(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The perspective of ’Praedicate Evangelium’ regarding liturgical abuses ABSTRACT: The paper examines the transformations made by the Ap. const. Praedicate Evangelium [= EP] regarding the contrast of liturgical abuses. Beginning with the problem of celebratory propriety that emerged in the context of postconciliar disbandment, it first examines the essential features of the case of abusiveness (the frequency of the conduct, the erroneous presumption of justification for the conduct, and the prominence of the authoritative condition) and, then, the main magisterial and papal directive interventions. Article 66 PB outlined a specific supervisory function on the part of the Congregation for Worship. PE, indulging the criterion of decentralizing co-responsibility, stimulates awareness of its own attributions and the specific responsibility of the bishops in ensuring the observance of liturgical norms. Article 96 EP therefore makes explicit the duties of the episcopal office and the supporting and assisting role of the Dicastery. The elimination of abusiveness is expressly linked with increased liturgical formation. The normative change does not change the essence of ecclesial discipline; however, it requires a qualitative leap in the pastoral solicitude of bishops (the most significant contribution is the deontological call). An in-depth theoretical and practical study of the problem of liturgical abusiveness, without trespassing on casuistry, can help complete the cultural and regulatory turnaround underway. SOMMARIO: 1. Il sentito problema della correttezza celebrativa - 2. L’inquadramento della fattispecie abusiva - 3. Gli interventi magisteriali e direttivi pontifici - 4. La disciplina dell’art. 66 della ‘Pastor bonus’ - 5. Il nuovo approccio di ‘Praedicate Evangelium’ - 5.1. Il contesto della riforma curiale - 5.2. L’art. 96 di ‘Praedicate Evangelium’ - 5.3. La responsabilità episcopale - 6. L’opportuno collegamento con la formazione liturgica - 7. Un mutamento disciplinare o attitudinale?